The impact of Namibia’s income tax reform: A CGE analysis - Chiripanhura, Blessing; Chifamba, Ronald (International Food Policy Research Institute, 2015)
This paper uses a computable general equilibrium (CGE) model to analyze and quantify the economy-wide equity and distributional impacts of Namibia’s tax policy reforms introduced in 2013. The effects of the reductions in personal and corporate taxes varied across institutions and markets. For households, a decrease in the effective tax rate directly resulted in higher disposable incomes, especially for urban households that participate in the labor market. Benefits to rural households were lower, principally because of their reliance on subsistence farming and mixed incomes. Households also benefited from falling consumption prices, thus experiencing improvements in their consumption patterns. Further, households experienced increasing returns to labor, but falling employment in the primary and service sectors. Given Namibia’s high unemployment rates, especially among those with little or no education, the tax cut enhanced inequality between skilled and unskilled labor. The tax reforms also resulted in exchange rate depreciation, thus increasing export competitiveness. On the other hand, the country’s reliance on imports meant that the high import bill exerted pressure of the country’s foreign currency reserves. Sectoral analysis shows that the manufacturing sector tended to benefit more from the reforms than other sectors. Output from manufacturing activities increased, together with manufacturing exports. The tax changes appeared to support the national policy of promoting manufacturing activities.